Nature and symbol through useable approach in the novel Harga Sebuah Maruah - Ishak, Nadia; Kamarudin, Kamariah; Mohd. Kiram, Norazlina; Abdul Rahman, Haliza (Human Resource Management Academic Research Society, 2021)
Since centuries ago, the Malay community is synonym with nature that has a bonding tie. The nature becomes part of the lives for the Malay community and both rely on each other for living. Thus, this bonding makes the Malay community very sensitive towards the surrounding, incident or event that happens. In this context the Malay community will immediately reacts and connect towards whatever is happening in nature as an exemplary on their daily lives. Therefore, this article is to show that element of nature as a symbol in describing something meaningful or things. This research is based on the novel of Harga Sebuah Maruah (2007) authored by Azizi Haji Abdullah. This journal uses Usable Approach which is in the theory of Pengkaedahan Melayu as an analysing framework. It points on literature as a nature object which events has its course and functions in a way to benefits in the daily living of mankind. The theory of Pengkaedahan Melayu generated by Hashim Awang emphasizes on the way of live, believe and culture of the Islam community. This research shows that Usable Approach is appropriate to be absorbed in this research in showing that element of nature as a symbol in describing something meaningful or things by using the principle which is in the Usable Approach.